2015
DOI: 10.4236/health.2015.79124
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Nutritional Status and Functional Capacity for Older People

Abstract: Functional capacity is the condition of an individual living independently and the lack of it for preparing and eating food, which is a factor that can result in malnutrition and deserves the attention of professionals and his family members. Then, the aim of this work was to evaluate the relationship between nutritional status and functional capacity for older adults using anthropometric measures and questionnaires for activities of daily and instrumental living. It was an epidemiological cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…La fuerza prensil de la mano se asoció con el estado nutricional de los participantes, sumándose así a las sugerencias expuestas por otros autores sobre el uso de la dinamometría como parte de la valoración nutricional de los adultos mayores (35,37).…”
Section: Discussionunclassified
“…La fuerza prensil de la mano se asoció con el estado nutricional de los participantes, sumándose así a las sugerencias expuestas por otros autores sobre el uso de la dinamometría como parte de la valoración nutricional de los adultos mayores (35,37).…”
Section: Discussionunclassified
“…Decreasing nutritional status is considered the first event that can lead to increased dependency of elderly. Thus, there is a possibility that decrease in food intake can lead to reduced independence in carrying out daily activities, thinning of muscle mass, and the occurrence of malnutrition (21) . The loss of physical capacity will occur along with reduced mobility and limitations in carrying out daily activities such as shopping, cooking and eating so that it will have an impact on nutritional status (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, impaired functional capacity may be an indicator of nutritional risk (Dehghankar, Shahrokhi, Oveisi, Esmailzadehha, & Ghorbani, 2016), particularly among older inpatients since hospitalization aggravates functional and cognitive decline (Mendes et al, 2016). Souza et al (2015) concluded that older people's independence to perform basic and instrumental activities of daily living was associated with a healthy weight. Similarly, Tramontano et al (2016) reported that the physical performance and functional status of older people were significantly associated with their nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…Self-care deficit is influenced by intrinsic factors, such as age, and multiple extrinsic factors, which include, for the purposes of this study, diseases that require hospitalization and surgical intervention. The decline in functional capacity is mostly associated with lower food intake and decreased muscle mass and strength (Fried et al, 2001;Souza et al, 2015). Thus, impaired functional capacity may be an indicator of nutritional risk (Dehghankar, Shahrokhi, Oveisi, Esmailzadehha, & Ghorbani, 2016), particularly among older inpatients since hospitalization aggravates functional and cognitive decline (Mendes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation